RETRACTED: Monitoring Air Pada Water Torn Berbasis Android dan Mikrokontroller - Anggie Meifriyan Pratama; Dwiny Meidelfi; Deddy Prayama (SOTVI - Society of Visual Informatics, 2020)
Control and monitoring of water in a tank is a computer instrumentation needed in industry. This final project discusses a water monitoring application in water tornautomatically based on android and supported by a microcontroller. One of the developing technology fields is microcontroller technology. In designing this device, it uses a NodeMCU microcontroller as a data processor and an ultrasonicsensor as data input as well as a buzzer and servo. An ultrasonic sensor is a devicethat can measure the distance of an object by utilizing reflected ultrasonic waves. This water monitoring uses firebase as a database to store data. To displaymeasurement data, the interface is also designed using the Android Studioapplication software in the form of graphs, pump status, and water notifications.The test results show that the ultrasonic sensor used is able to measure water levels from 2 cm to 20 cm with an average measurement error of 4.93%. Water monitoringis designed to be able to produce a system output response according to thereference value given. In addition, water level monitoring can be displayed on the Android software interactively